Biochemical and Histological Evidence on the Protective Effects of Allium hirtifolium Boiss (Persian Shallot) as an Herbal Supplement in Cadmium-Induced Hepatotoxicity. (17th June 2020) - Omidifar, Navid; Nili-Ahmadabadi, Amir; Gholami, Ahmad; Dastan, Dara; Ahmadimoghaddam, Davoud; Nili-Ahmadabadi, Hossein
Abstract : Background and Objectives . Allium hirtifolium Boiss (Persian shallot), as an edible vegetable, has several pharmacological properties including antimicrobial, anti-inflammatory, and antioxidative effects, while its protective effects in liver cells are controversial. In this study, we examined the effect of A. hirtifolium extract on cadmium- (Cd-) induced hepatotoxicity in rats. Materials and Methods . Thirty-six male Wistar rats were divided into six groups: groups 1, 2, and 3 received vehicle, Cd (100 mg/L/day by drinking water), and A. hirtifolium extract (200 mg/kg/day; orally), respectively. Groups 4, 5, and 6 were Cd groups which were treated with A. hirtifolium extract (50, 100, and 200 mg/kg/day, respectively). After 2 weeks, liver enzymes such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) and also oxidative stress biomarkers including lipid peroxidation (LPO), total antioxidant capacity (TAC), total thiol molecule (TTM), and the histopathological changes were determined using standard procedure. Results . The findings showed that Cd caused a remarkable rise in levels of serum hepatic enzymes such as ALT (P < 0.001 ), AST (P < 0.01 ) and ALP (P < 0.001 ) compared with the control group. In addition, Cd led to the decreasing of the levels of TTM (P < 0.001 ) and TAC (P < 0.001 ) and increasing of LPO (P < 0.001 ) in liver tissue in comparison with the control group. In this regard, remarkable vascular congestion, hepatocellular degeneration, and vacuolization were observed in hepatic tissue of Cd-treated rats. Following the administration of A. hirtifolium extract, a significant improvement was observed in the functional and oxidative stress indices of hepatic tissue alongside histopathologic changes. Conclusion . The current study indicated that the A. hirtifolium extract might prevent hepatic oxidative injury by improving oxidant/antioxidant balance in rats exposed to Cd.